The impact of the LaSalle Judgement on Share Price Reactions - Schreuder, Kirsten (Student Undergraduate Research E-journal!, 2015)
The Supreme Court in LaSalle acknowledged an exception to the “Absolute Priority Rule” for “new value contributions” on condition of a “market test”. This study examined the impact of the “market test” on share price reactions with regard to Chapter 11 bankruptcy filings in the United States. This study found that the share price reactions were stronger for the period after LaSalle. However, the effect of the “market test”, determined by my model, was not statistical significant. The results suggests that future research on the “market test” should use a channel which is more directly linked to “absolute priority deviations”.